Natural nanofibers embedded in the seed mucilage envelope: composite hydrogels with specific adhesive and frictional properties - Agnieszka Kreitschitz; Stanislav N. Gorb (Beilstein Journal of Nanotechnology)
The increasing interests in natural, biodegradable, non-toxic materials that can find application in diverse industry branches, for example, food, pharmacy, medicine, or materials engineering, has steered the attention of many scientists to plants, which are a known source of natural hydrogels. Natural hydrogels share some features with synthetic hydrogels, but are more easy to obtain and recycle. One of the main sources of such hydrogels are mucilaginous seeds and fruits, which produce after hydration a gel-like, transparent capsule, the so-called mucilage envelope. Mucilage serves several important biological functions, such as supporting seed germination, protecting seeds against pathogens and predators, and allowing the seed to attach to diverse surfaces (e.g., soil or animals). The attachment properties of mucilage are thus responsible for seed dispersal. Mucilage represents a hydrophilic, three-dimensional network of polysaccharides (cellulose, pectins, and hemicelluloses) and is able to absorb large amounts of water. Depending on the water content, mucilage can behave as an efficient lubricant or as strong glue. The current work attempts to summarise the achievements in the research on the mucilage envelope, primarily in the context of its structure and physical properties, as well as biological functions associated with these properties.